D‐Glucuronic Acid‐Coated Ultrasmall Paramagnetic Ln2O3 (Ln = Tb, Dy, and Ho) Nanoparticles: Magnetic Properties, Water Proton Relaxivities, and Fluorescence Properties. Issue 34 (29th August 2019) - Marasini, Shanti; Yue, Huan; Ho, Son Long; Jung, Ki‐Hye; Park, Ji Ae; Cha, Hyunsil; Ghazanfari, Adibehalsadat; Ahmad, Mohammad Yaseen; Liu, Shuwen; Jang, Yeong Ji; Miao, Xu; Chae, Kwon‐Seok; et al.
Abstract : Many of the lanthanide‐based nanoparticles are valuable in magnetic resonance imaging (MRI) because they have excellent magnetic properties that make them suitable for MRI contrast agents, while some of them have additional optical properties and thus can serve as fluorescence imaging (FI) agents as well. Herein, we synthesized d ‐glucuronic acid‐coated ultrasmall Ln2 O3 (Ln = Tb, Dy, and Ho) nanoparticles with average diameters of ∼ 2 nm. All the nanoparticles showed unsaturated but appreciable magnetization of ∼ 4 emu/g at an applied field of 1.8 T at room temperature, and consequently, high transverse water proton relaxivities ( r 2 ) of ∼ 7 s –1 mm –1 at 1.5 T, ∼ 35 s –1 mm –1 at 3.0 T, and ∼ 55 s –1 mm –1 at 9.4 T with negligible longitudinal water proton relaxivities ( r 1 ), thus being eligible for use as T2 MRI contrast agents at high MR fields. In addition, d ‐glucuronic acid‐coated ultrasmall Tb2 O3 nanoparticles exhibited fluorescence in the green region, useful for dual‐modal imaging. Abstract : d ‐glucuronic acid‐coated ultrasmall Ln2 O3 nanoparticles (Ln = Tb, Dy, and Ho) ( d avg = ∼ 2.0 nm) exhibited excellent r 2 values which increased with increasing MR field and were suitable for use as T2 MRI contrast agents, and in addition, d ‐glucuronic acid‐coated ultrasmall Tb2 O3 nanoparticles showed fluorescence in the visible region (i.e., green color) suitable for use as FI agent.